PERAN ORANGTUA DALAM MELAHIRKAN GENERASI ULUL ALBAB - Nihayati, Nihayati; Nurkhasanah, Nurkhasanah; Arnidha, Yunni; Budiarti, Yesi (Jurnal Dedikasi untuk Negeri, 2023)
Children are a mandate from God given to parents, children are assets in the afterlife for both parents. Parents are the main teachers in family life, children are like blank paper ready to be drawn and colored. So the purpose of this activity is that parents understand their role in educating, guiding and directing children to become the ulul albab generation in the midst of the onslaught of modern progress in various fields. This activity was carried out at Muhammadiyah Banyuwangi Elementary School, Banyumas, Pringsewu, Â with the target being guardians of students from grades 1 to grade 6. This activity used an active participatory method with several stages, namely the stages of observation, coordination with the school and implementation of activities. The result of this activity is that parents understand that current parenting challenges require parenting knowledge. The role of parents in forming the ulul albab generation is to accompany, establish communication, supervise, provide opportunities, provide motivation and direct. This is in line with the principles of parenting, namely good potential in children; exemplary, remind and improve; consistent; need love and patience.